The Extent of Commitment Banks with Basel Committee Standards (III) in Measuring Financial Risks to Improve the Quality of Financial Reports - Yassine, Zahida Ali (Finance and Business Economies Review, 2019)
Thi The increasing trend towards the application of globalization and financial liberalization and its associated market integration and free movement of capital make the issue of financial stability a top priority for countries. The Banking Control Committee was established in the early 1970s and, through its reports, seeks to strengthen the rigidity of financial stability and harmonize national regulatory systems and practices. The study aims at presenting the extent to which the Iraqi banks comply with Basel III standards in measuring financial risks, which improves the quality of financial reports and the information they reflect to users and customers. The conclusions of the study is the weakness of the investment resources of the bank while affecting the operational performance, which is the existence of a suitable security unit for accounting information if it was used predicatively, but it refers to the weakness of the investment power of banks and the operation of depositors funds in a good way. s study aims at highlighting the role played by green marketing in supporting the social responsibility of economic enterprises as they have common objectives that serve the interests of societies. The descriptive approach was used to inform the theoretical aspect of corporate social responsibility, green marketing and analysis to highlight the effect of green marketing on supporting the corporate social responsibility. The study concluded that green marketing enterprises can effectively support their social responsibility. As it found the hypothesis and considered green marketing as a vital approach to support social responsibility in the enterprises, to the green marketing mix supports corporate social responsibility through all of its elements (green product, promote, pricing and green distribution).